Role of tool design on thermal cycling and mechanical properties of a high-speed micro friction stir welded 7075-T6 aluminum alloy. (December 2019) - Ni, Y.; Fu, L.; Shen, Z.; Liu, X.C.
Abstract: AA7075-T6 sheet welds that were 0.5 mm thick were fabricated by micro friction stir welding (μFSW) using a pinless tool as well as a pin tool. The experiments were conducted at a higher rotational speed of 6000 rpm and a higher welding speed of 1200 mm/min than those that are used in conventional FSW. The heat generation, peak temperature and elevated-temperature exposure time (t150 ) of the joints fabricated by the pin tool were higher than those fabricated by the pinless tool at the same shoulder penetration depth. The minimum ratio of the thickness reduction at the center of the friction stir weld was 0% for the pinless tool at a penetration depth of 0.14 mm. In comparison to those for the joints fabricated by the pin tool, the joint fabricated by the pinless tool showed less softening and better tensile properties. For the welds fabricated by the pin tool, the tensile properties increased with increasing penetration depth. In the case of welds made by the pinless tool, the tensile specimens failed at the transition region between the stir zone and the thermomechanically affected zone on the retreating side due to the local thickness reduction. However, the tensile specimens failed at the center of the stir zone due to kissing bond defects in the joints produced by the pin tool.